Empathy in the Digital Age: Exploring Disinhibition, Phubbing, and Emotional Erosion in Online Communication - Hidayat, Rachmat (Communica : Journal of Communication, 2024)
The rapid growth of digital communication has reshaped interpersonal interaction and raised concerns about empathy in computer-mediated environments. This study examines how digital disinhibition, multitasking, and phubbing affect emotional presence and empathetic engagement. Using a mixed-methods design, quantitative data from 200 participants and qualitative interviews with 25 individuals were analyzed to provide comprehensive insights. Results show significantly lower empathy scores in online compared to face-to-face communication, with younger participants reporting higher rates of phubbing. Thematic analysis revealed emotional fatigue, attentional fragmentation, and disinhibition as major causes of relational disconnection. Generational and cultural differences further complicated the dynamics of empathy in digital settings. The study highlights the need for empathy-centered design in communication technologies. Recommended interventions include responsive interfaces, ethical frameworks such as the Ethics of Care, and user-centered practices. The findings call for a systemic redesign of digital platforms to strengthen attentiveness, emotional intelligence, and ethical engagement.